Кожаные башмаки: повесть / А. Л. Гарф - Гарф Анна Львовна (Детская литература, 1988)
Экземпляры: ф.12 (20160321) / Инвентарный номер: 027735 / Цена: 0.80 / Авт.знак: Г 21 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6